2016
DOI: 10.5539/ijbm.v11n12p1
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Analysis of Service Quality: Small Construction Business and Australian Household

Abstract: The survival rate of small businesses operating in the Australian building maintenance industry (SBBM) has been decreasing due to high competition. Some researchers identify the delivery of high levels of service quality as a differential strategy that can improve small business chances of survival. The objective of this study is to examine the nature of the relationships between the quality of service delivered by SBBM and the satisfaction and repurchase intention of Australian households. Additionally, provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As research in the realm of service quality in the integrated construction industry started to see the emergence of conceptual frameworks since 1994, this study intends to review 30 notable studies from this time. Therefore, this review includes the works of (SQ01) Baker and Lamb (1994), (SQ02) Samson and Parker (1994), (SQ03) Nelson and Nelson (1995), (SQ04) Buttle (1996), (SQ05) Preece and Tarawneh (1997), (SQ06) Winch et al (1998), (SQ07) Garland et al (1999), (SQ08) Holm (2000a), (SQ09) Holm (2000b), (SQ10) Hoxley (2000), (SQ11) Love et al (2000), (SQ12) Siu et al (2001), (SQ13) Maloney (2002), (SQ14) Arditi and Lee (2003), (SQ15) Arditi and Lee (2004), (SQ16) Dabholkar and Overby (2005), (SQ17) Sui Pheng and Hui Hong (2005), (SQ18) Oliver (2006), (SQ19) Marja Rasila and Florian Gersberg (2007), (SQ20) Forsythe (2007), (SQ21) Forsythe (2008), (SQ22) Tuzovic (2009), (SQ23) Seiler and Reisenwitz (2010), (SQ24) Araloyin and Olatoye (2011), (SQ25) Forsythe (2012), (SQ26) Lai and Lai (2013), (SQ27) Sunindijo et al (2014), (SQ28) Forsythe (2015), (SQ29) Eldejany (2016), and (SQ30) Forsythe (2016). Note that SQ stands for studies in “service quality with reference to the integrated construction industry”, and it has been chronologically serialized from SQ01 to SQ30 for the purpose of tabulation (Table I).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…As research in the realm of service quality in the integrated construction industry started to see the emergence of conceptual frameworks since 1994, this study intends to review 30 notable studies from this time. Therefore, this review includes the works of (SQ01) Baker and Lamb (1994), (SQ02) Samson and Parker (1994), (SQ03) Nelson and Nelson (1995), (SQ04) Buttle (1996), (SQ05) Preece and Tarawneh (1997), (SQ06) Winch et al (1998), (SQ07) Garland et al (1999), (SQ08) Holm (2000a), (SQ09) Holm (2000b), (SQ10) Hoxley (2000), (SQ11) Love et al (2000), (SQ12) Siu et al (2001), (SQ13) Maloney (2002), (SQ14) Arditi and Lee (2003), (SQ15) Arditi and Lee (2004), (SQ16) Dabholkar and Overby (2005), (SQ17) Sui Pheng and Hui Hong (2005), (SQ18) Oliver (2006), (SQ19) Marja Rasila and Florian Gersberg (2007), (SQ20) Forsythe (2007), (SQ21) Forsythe (2008), (SQ22) Tuzovic (2009), (SQ23) Seiler and Reisenwitz (2010), (SQ24) Araloyin and Olatoye (2011), (SQ25) Forsythe (2012), (SQ26) Lai and Lai (2013), (SQ27) Sunindijo et al (2014), (SQ28) Forsythe (2015), (SQ29) Eldejany (2016), and (SQ30) Forsythe (2016). Note that SQ stands for studies in “service quality with reference to the integrated construction industry”, and it has been chronologically serialized from SQ01 to SQ30 for the purpose of tabulation (Table I).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some essential learning points are as follows: Several authors have suggested that service quality is a hierarchical construct. However, very few like Sunindijo et al (2014) have attempted for original measurement for construct service quality. Almost all studies have made an attempt to review prior literature relating to service quality in the domain of integrated practice. Most of the empirical studies since 2008 have involved tenants and customers as respondents in applying hierarchical representation using SERVQUAL-based dimensions. Only Sunindijo et al (2014) applied EFA in the domain of integrated construction industry. No study has been reported so far using CFA showcasing psychometric properties of the service quality scale. Although some studies have attempted to develop a link for measuring customer satisfaction and patronage intension, only recently adequate theoretical foundations have been seen postulated for structural relations among constructs relating to service quality (Sunindijo et al , 2014; Eldejany, 2016). …”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation